Long-term lntraspinal Infusions of Opioids with a New Implantable Medication Pump - Likar, Rudolf; Spendel, Martin C; Amberger, Walter; Kepplinger, Berthold; Supanz, Sabine; Sadjak, Anton (Arzneimittelforschung, 1999)
Experiences with long-term intraspinal infusion of opioid drugs using the new implantable medication pump VIP 30 in patients with chronic non-malignant pain are reported. During a 19-month period 10 patients with chronic pain - mainly mixed nociceptive-neuropathic pain - underwent implantation of the medication pump for long-term treatment. The mean followup period was 9.5 months. Pain relief was classified as very good in 22.2%, good in 44.4%, moderate in 22.2% and poor in 11.1%. In 88.9% of the cases the patients stated they would undergo the same procedure again. Technical problems (catheter dislocation) developed in patients could be surgically corrected. One pump including catheter was explanted because of an infected seroma within the pocket area. Long-term intrathecal application of opioids with the VIP 30 pumps is an effective and safe treatment in patients with chronic non-malignant pain.
Keywords: Implantable medication pump, pain relief; Opioids, intrathecal; Pain, chronic non-malignant; VIP 30